2015
DOI: 10.4103/2347-8659.149420
|View full text |Cite
|
Sign up to set email alerts
|

Central somatosensory conduction slowing in adults with isolated elevated plasma level of homocysteine

Abstract: Aim: Elevated plasma level of homocysteine (eHcy) is a recognized risk factor for dementia. However, whether the central conduction is affected in patients with an isolated eHcy is unknown. In this study, we addressed whether central conduction is altered in adults with eHcy. Methods: Evoked potential studies including somatosensory (SSEP), visual (VEP) and brainstem auditory evoked potentials (BAEP), were performed to evaluate central conduction in patients with isolated eHcy. Results: Nine SSEP, 7 VEP, and 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…Neurophysiologic studies of patients with eHcy-induced PN showed evidence of mildly mixed demyelination and distal axonal degeneration, suggestive of a mild largefiber sensorimotor neuropathy [6]. Interestingly, central somatosensory large fibers may also be involved [7]. eHcy exerts neurotoxic effects causing neuronal injury by overstimulating NMDA receptors, inducing calcium influx [8] which provokes excitotoxic and oxidative stress, damages DNA and leads to neuronal death or apoptosis, which has been demonstrated in laboratory in vitro cell culture and in vivo animal studies [9].…”
Section: Discussionmentioning
confidence: 99%
“…Neurophysiologic studies of patients with eHcy-induced PN showed evidence of mildly mixed demyelination and distal axonal degeneration, suggestive of a mild largefiber sensorimotor neuropathy [6]. Interestingly, central somatosensory large fibers may also be involved [7]. eHcy exerts neurotoxic effects causing neuronal injury by overstimulating NMDA receptors, inducing calcium influx [8] which provokes excitotoxic and oxidative stress, damages DNA and leads to neuronal death or apoptosis, which has been demonstrated in laboratory in vitro cell culture and in vivo animal studies [9].…”
Section: Discussionmentioning
confidence: 99%